Use of biomarkers to establish potential role and function of circulating microRNAs in acute heart failure. (1st December 2016) - Vegter, Eline L.; Schmitter, Daniela; Hagemeijer, Yanick; Ovchinnikova, Ekaterina S.; van der Harst, Pim; Teerlink, John R.; O'Connor, Christopher M.; Metra, Marco; Davison, Beth A.; Bloomfield, Daniel; Cotter, Gad; Cleland, John G.; et al.
Abstract: Background: Circulating microRNAs (miRNAs) emerge as potential heart failure biomarkers. We aimed to identify associations between acute heart failure (AHF)-specific circulating miRNAs and well-known heart failure biomarkers. Methods: Associations between 16 biomarkers predictive for 180 day mortality and the levels of 12 AHF-specific miRNAs were determined in 100 hospitalized AHF patients, at baseline and 48 hours. Patients were divided in 4 pre-defined groups, based on clinical parameters during hospitalization. Correlation analyses between miRNAs and biomarkers were performed and complemented by miRNA target prediction and pathway analysis. Results: No significant correlations were found at hospital admission. However, after 48 hours, 7 miRNAs were significantly negatively correlated to biomarkers indicative for a worse clinical outcome in the patient group with the most unfavorable in-hospital course (n = 21); miR-16-5p was correlated to C-reactive protein (R = − 0.66, p-value = 0.0027), miR-106a-5p to creatinine (R = − 0.68, p-value = 0.002), miR-223-3p to growth differentiation factor 15 (R = − 0.69, p-value = 0.0015), miR-652-3p to soluble ST-2 (R = − 0.77, p-value < 0.001), miR-199a-3p to procalcitonin (R = − 0.72, p-value < 0.001) and galectin-3 (R = − 0.73, p-value < 0.001) and miR-18a-5p to procalcitonin (R = − 0.68, p-value = 0.002). MiRNA target prediction and pathway analysis identified several pathways related to cardiac diseases, which could be linked to some of the miRNA-biomarker correlations. Conclusions: The majority of correlations between circulating AHF-specific miRNAs were related to biomarkers predictive for a worse clinical outcome in a subgroup of worsening heart failure patients at 48 hours of hospitalization. The selective findings suggest a time-dependent effect of circulating miRNAs and highlight the susceptibility to individual patient characteristics influencing potential relations between miRNAs and biomarkers.